A new class of porous materials for efficient CO2 separation: Ionic liquid/graphene aerogel composites. (January 2021) - Zeeshan, Muhammad; Yalcin, Kaan; Sarac Oztuna, F. Eylul; Unal, Ugur; Keskin, Seda; Uzun, Alper
Abstract: Here, we report a new post-synthesis modification strategy for functionalizing reduced graphene aerogels (rGAs) towards an exceptional CO2 separation performance. 1- N -butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6 ]) was impregnated on a rGA, prepared by reducing GA at 700 °C, at various ionic liquid (IL) loadings of 5, 10, 30, and 50 wt%. The resulting composites were characterized in deep detail by X-ray photoelectron spectroscopy, X-ray diffraction, N2 physical adsorption measurements, scanning electron microscopy, Fourier transform infrared and Raman spectroscopies, and thermogravimetric analysis. Results indicated the presence of interactions between the rGA surface and the anion of the IL, potentially improving the CO2 affinity. Volumetric gas adsorption measurements using these materials showed that the deposition of [BMIM][PF6 ] on rGA surface at an IL loading of 50 wt% boosts the CO2 /CH4 selectivity by more than 20-times, exceeding an absolute value of 120, a remarkably higher CO2 /CH4 selectivity compared to that of other functionalized materials under similar operating conditions. Tunability of both the IL structure and the surface characteristics of rGA offer a tremendous degree of flexibility for the rational design of these IL/rGA composites towards high performance in gas separation applications. Graphical abstract: 1- N -butyl-3-methylimidazolium hexafluorophosphate ([BMIM][PF6 ]) deposited on the surface of a reduced graphene aerogel (rGA) improves the CO2 /CH4 selectivity of rGA by more than 20-times. Image 1 Highlights: Ionic liquid/reduced graphene aerogel (IL/rGA) composites were introduced. 50 wt% IL loading was achieved owing to 3D macrostructure of rGA. IL impregnation offered more than 20-times increase in CO2 /CH4 selectivity of rGA. Tunability of rGA and IL offer a great promise for gas separation using IL/rGAs.